Winning and losing: Causes for variability in outcome of fights in male Magellanic penguins (Spheniscus magellanicus) - Renison, Daniel (2002)
Game theory models predict that fighting ability should be more important in contest outcome when the payoffs of winning are high for both contestants, and ownership should be more important when payoffs are low. Male Magellanic penguins (Spheniscus magellanicus) provide an opportunity to test these predictions in a natural setting because payoffs of winning are higher for penguins fighting before egg laying and lower for penguins fighting after egg laying, allowing the prediction of differences in who should win and lose. We watched an area of approximately 2000 Magellanic penguin nests from 1992 to 1996 at Punta Tombo breeding colony, Argentina; we quantified fighting behavior, banded contestants, measured their body size (here used as an index of fighting ability), determined ownership status when possible, and monitored their reproductive success. We determined that male Magellanic penguins fought for nests and mates. As theory predicts, before egg laying, body size difference was more important than ownership as a predictor of contest outcome and fight duration. After egg laying, owners won fights, and size did not predict who won or how long they fought. Our comparisons of nest ownership, nest quality, and chicks fledged by winners and losers suggested that our predictions on the change in benefits of winning before and after egg laying were correct. We conclude that game theory models are useful in predicting who won or lost fights in male Magellanic penguins and that ultimate benefits of winning fights are related to fitness.